(3GdCSHGH h GdMdhd hab eHGOF GdGbJUGO GdGSdGejs - (3hVGM fLjH(B, (3QLHs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2010)
(3eaghe GdJVNe h CfhGYg , CSHGH GdJVNe h BKGQg , GdYdGL GdGbJUGOj GdhVYj ddJVNe h GdYdGL GdGbJUGOj GdGSdGej dg (B.s
(3eQGLY U(B.297s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdJVNe GdeGdjs; (3GdQchO GdGbJUGOjs